The Magnitude of Diving Bradycardia During Apnea at Low-Altitude Reveals Tolerance to High Altitude Hypoxia - Holmström, Pontus; Mulder, Eric; Sundström, Angelica Lodin; Limbu, Prakash; Schagatay, Erika (Frontiers in Physiology, 2019)
Acute mountain sickness (AMS) is a potentially life-threatening illness that may develop during exposure to hypoxia at high altitude (HA). Susceptibility to AMS is highly individual, and the ability to predict it is limited. Apneic diving also induces hypoxia, and we aimed to investigate whether protective physiological responses, i.e., the cardiovascular diving response and spleen contraction, induced during apnea at low-altitude could predict individual susceptibility to AMS. Eighteen participants (eight females) performed three static apneas in air, the first at a fixed limit of 60 s (A1) and two of maximal duration (A2–A3), spaced by 2 min, while SaO2, heart rate (HR) and spleen volume were measured continuously. Tests were conducted in Kathmandu (1470 m) before a 14 day trek to mount Everest Base Camp (5360 m). During the trek, participants reported AMS symptoms daily using the Lake Louise Questionnaire (LLQ). The apnea-induced HR-reduction (diving bradycardia) was negatively correlated with the accumulated LLQ score in A1 (rs = −0.628, p = 0.005) and A3 (rs = −0.488, p = 0.040) and positively correlated with SaO2 at 4410 m (A1: r = 0.655, p = 0.003; A2: r = 0.471, p = 0.049; A3: r = 0.635, p = 0.005). Baseline spleen volume correlated negatively with LLQ score (rs = −0.479, p = 0.044), but no correlation was found between apnea-induced spleen volume reduction with LLQ score (rs = 0.350, p = 0.155). The association between the diving bradycardia and spleen size with AMS symptoms suggests links between physiological responses to HA and apnea. Measuring individual responses to apnea at sea-level could provide means to predict AMS susceptibility prior to ascent.